Mismatch Between Exposure Risk and Protection: Occupational Inequities in COVID-19 Prevention Among Field-Based Utility Workers in South Africa - Tanusha Singh; Patrick Zibaya (Journal of Occupational & Environmental Medicine, 2026)
Objective: Field-based workers faced unique occupational risks during the COVID-19 pandemic. This study assessed occupational disparities in COVID-19 exposure, vaccination uptake, PPE adequacy and implementation of preventive measures among utility workers. Methods: A cross-sectional analytical study was conducted among 154 South African workers in a power distribution company. Data were collected using a questionnaire and analysed using multivariable logistic regression to estimate adjusted odds ratios. Results: Technical workers had significantly higher workplace exposure and lower vaccination uptake compared with managerial staff. Adjusted models showed reduced odds of vaccination among technical workers (aOR 0.48, 95% CI 0.25–0.91). Perceived PPE adequacy was also significantly lower among high-exposure groups. PPE availability and training were significant predictors of adherence to preventive measures. Conclusion: A mismatch exists between occupational exposure and protection, requiring targeted, context-specific occupational health strategies.